Firm Heterogeneity and Endogenous Regional Disparities - Carlo Altomonte; Italo Colantone (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2005)
We exploit the census of Romanian firms to provide a microfounded analysis of the sources of regional disparities in the country. To this extent, we adapt to the regional case a decomposition of firm-level output dynamics based on semi-parametric productivity estimates. The methodology, robust to different techniques of TFP estimation, allows us to analyze the sources of regional disparities controlling for the heterogeneity in firms?characteristics. In particular, we measure various compositional effects of multinational enterprises (MNEs)on regional growth, finding that regional disparities are to a large extent endogenous to the interaction between firm-level dynamics and initial market conditions.
Keywords: F12; F23; L10; P20; 330; regional convergence; multinational firms; productivity; transition economies.; Regionale Entwicklung; Multinationales Unternehmen; Übergangswirtschaft; Rumänien